Lesbians in Television and Text after the Millennium - Beirne, R. author. aut Link
XII, 233 p.
Keywords: Taking up such issues as mainstreaming, the male gaze, and female masculinity, this book puts forward provocative readings of little explored texts and offers new insights into the contemporary representation of lesbians.